Mineral chemistry of late Variscan gabbros from central Spain: constraints on crystallisation processes and nature of the parental magmas - Orejana, David; Losantos, Emma; Villaseca, Carlos; Jeffries, Teresa E (Journal of Iberian Geology, 2015)
Major and trace element chemistry has been determined in the main minerals (olivine, orthopyroxene, clinopyroxene, plagioclase, amphibole, phlogopite) from the Talavera and La Solanilla gabbroic intrusions (Spanish Central System). The results show a heterogeneous mineral composition illustrative of the chemical evolution of calc-alkaline basic magmas during crystallization. The formation of incompatible element-rich interstitial minerals, such as amphibole, phlogopite and accessory phases (e.g., zircon, apatite), and the presence of zoning patterns in major minerals towards a more evolved composition, point to a progressive differentiation of the parental melt. The chemical variation depicted by trace elements usually incompatible with clinopyroxene (e.g., rare earth elements (REE), Th, Zr, Nb, Ti) implies co-precipitation with phases displaying a compatible behaviour with respect to these elements (e.g., apatite, zircon, amphibole). However, the very high LILE (large ion lithophile elements) and LREE (light REE) shown by clinopyroxene can not be explained exclusively by a closed-system in-situ crystallization process. Several features of the mineral chemistry (e.g. positive correlation of (La/Sm)N with La and Na in clinopyroxene and plagioclase, respectively) support the involvement of an external component (wall-rock assimilation or hybridization with an evolved melt). The petrography and mineral chemistry of the gabbros, in conjunction with bulk rock data from previous studies, favour a calc-alkaline affinity for the parental melts. Thus, metasomatism in the mantle sources related with this basic magmatism might be associated with recycling of crustal components during the Variscan orogeny.